Causes and Effects of Working Long Hours: A Case Study of Young Bank Employees in China - Chen, Haisheng (2007)
The aim of this research is to investigate the causes and consequences of working long hours in China, especially as it affects recent graduates who are employed by Chinese banks. In order to successfully realise this aim, the objectives include: identifying the "long-hour culture" and how it applies in China; establishing the negative effects of working long hours on individuals; investigating how individuals are balancing their professional and personal lives; determining if job security (or insecurity) has an impact on the long-hour culture in China; applying these findings to young employees of Chinese banks. Ultimately, this research seeks to draw specific conclusions regarding how recent graduates employed by Chinese banks are impacted by the long-hour culture. By identifying how they view their work-life balance as well as whether they are motivated strictly by monetary rewards or if non-financial rewards are just as important, should prove beneficial to future students and researchers.